Health and Health Care in the U.S. Virgin Islands: Challenges and Perceptions - Callwood, Gloria B. (2012)
This research was designed to discover how residents of the United States Virgin Islands think about their health, health status, health problems, and the quality of the health care delivery system. Six focus groups were organized - one for males and one for females on each of the largest islands (St. Thomas, St. Croix, and St. John). Results indicated that Virgin Islanders see a large role for personal responsibility in achieving and maintaining good health, although there are cultural and economic barriers that prevent taking full advantage of available health services. Residents are especially concerned about privacy and threats to confidentiality of patient information that could occur among professionals.